Using deterministic record linkage to link ambulance and emergency department data: is it possible without patient identifiers? - Sophie Jane Clark; Mary Halter; Alison Porter; Holly Christina Smith; Martin Brand; Rachael Fothergill; Jaqualine Lindridge; Martin McTigue; Helen Snooks (International Journal of Population Data Science, 2019)
Introduction Routine linkage of emergency ambulance records with those from the emergency department is uncommon in the UK. Our study, known as the Pre-Hospital Emergency Department Data Linking Project (PHED Data), aimed to link records of all patients conveyed by a single emergency ambulance service to thirteen emergency departments in the UK from 2012-2016.